Sedimentology and Structural Geology of Ayer Hitam area, Johor - HASSAN, ASIYAHTUL HUSNA (2016)
Geological study has been conducted at Ayer Hitam area, Johor which is mentioned before as the Gemas Formation from the previous studies by the geologist. However, there’s a claimed by Kamal Roslan (1990, 1996) who categorized that Ayer Hitam rock distribution is the same formation as Semantan Formation which mainly distributed at Temerloh area, center of Central Belt. There are lots of publication and intensive study focusing on Semantan Formation but less publication about sedimentology of Triassic Formations at the other parts than Central Pahang in Central belt. Therefore, correlation and similarity of rock successions of Ayer Hitam area with Semantan Formation are yet to be found. Previously Semantan Formation is mentioned as fore arc acrretionary by Hutchison (1989) however recent studies shows it is foreland basin (Madon, 2010). Therefore, by focusing on sedimentology of the area including facies analysis, its sedimentary structure and also in structural geology will give understanding of sedimentology of this area will allow interpreting the possible depositional environment of this place thus comes out with the depositional model.